Pengaruh Komunikasi, Lingkungan Kerja, Pengembangan Sumber Daya Manusia Dan Motivasi Terhadap Semangat Kerja (Studi Kasus pada Pegawai Gudang Anteraja Malang) - Nanda Purnama; Nurhidayah Nurhidayah; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study is to find out the description of communication, work environment, human resource development, motivation and work spirit. To know and analyze the impact of communication, work environment, human resource development, motivation and morale. To find out and analyze the impact of communication on morale. To find out and analyze the impact of the work environment on morale. To find out and analyze the impact of human resource development on morale.This study uses a saturated sample, namely all employees of PT. Anteraja Malang, totaling 40. The results of this study indicate that communication, work environment, human resource development, motivation have a significant effect on work morale. work communication has a positive and significant effect on work morale. Work environment has a positive and significant effect on work morale. Human Resource Development has a positive and significant effect on work morale. Motivation has a positive and significant effect on work morale. Keywords: Influence, Communication, Work Environment, Human Resource Development, Motivation